Devotion In Nicholas Sparks' The Notebook (1996): An Individual Psychological Approach - Fajarini, Yuli Andria, Dr. Phil. Dewi Candraningrum, M.Ed, Titis Setyabudi, S.S., M.A (2015)
The study is purposed to show the devotion of Noah Calhoun, the main character in Nicholas Sparks': The Notebook. The object of the study of this research is to analyze the novel based on its structural elements and the devotion of Noah that deals with inferiority feeling and compensation, striving for superiority, fictional finalism, style of life, social interest, and creative self using an individual psychological approach. This research is qualitative research. Type of data of the study is text taken from two data sources: primary and secondary. The primary data source is taken from the novel The Notebook written by Nicholas Sparks in 1996. While the secondary data sources are other sources related to the primary data. Data collecting method in this study is library research, and in analyzing the data the researcher employs descriptive analysis. The result of the study shows the following conclusion. Based on individual psychology analysis the novel tells that the major character, Noah Calhoun is affected by the psychological effect. Noah fights hard to get his true love and shows her his devotion. He dedicates all of his live for her, Allie.